COAL SEAM ANALYSIS WEST BATURAJA SUB-DISRICT, SOUTH SUMATERA - Ganjar Gani, Reza Mohammad; Firmansyah, Yusi (Faculty of Geological Engineering, Universitas Padjadjaran, 2018)
Sumatera island is located between 3 NH to 6 SH and 96 EL to 106 EL, along 1,700 km northernto the South, parallel to the subduction zone between the Sunda plate and Indian Oceanic plate onthe western part of Sumatera Island. The western part of Sumatera Island is a fore deep basin.Parallel to it is the Bukit Barisan chain. Towards the eastern part, there is the foreland basin ofNeogen. At the central zone of Bukit Barisan chain, there is the in-between basin. The SouthSumatera Basin starts from the eastern part of Bukit Barisan stretching to the south-east of theocean and adjoining to the basin at the boundary of Bukit Barisan in the south-west and tertiarySunda Basin in the south-east. Coal at the basin or on this formation with low rank is generallylignite. It is only at the young andesite intrusion (at Bukit Asam) where this lignite is altered to behigh rank coal. On this formation coal is divided into three groups, namely, upper part (6 – 7 seams),central part, and lower part (8 – 10 seam). The coal development is mainly autochthon, in the forestenvironment where there is no indication of the existence of swamp vegetation element. Based onthe data, it can be concluded that coal resource at the survey location has quite good quality, withmoderate calorific value and low sulphuric content. Thus, it can be classified into the ‘brown coal’.